Penerapan Standart Operasional Prosedur Divisi Keuangan Dalam Proses Penerimaan Dan Pengeluaran Kas PT. Inovasi Teknologi Solusindo (Trustmedis) - Safitri, Ismi Dwi; Purwanto, Sugeng (Innovative: Journal Of Social Science Research, 2025)
This study examines the implementation of Standard Operating Procedures (SOP) in the Finance Division of PT. Inovasi Teknologi Solusindo (Trustmedis), focusing on the processes of cash receipts and disbursements. SOPs play an essential role in ensuring orderly financial administration while minimizing errors and the risk of fund misuse. A descriptive qualitative approach was applied, with data collected through observation, interviews, and documentation study. The findings reveal that SOPs have been implemented systematically, covering stages such as invoice creation, document verification, payment authorization, and transaction recording. However, the study identified several challenges, including limited employee understanding of certain procedures. Therefore, regular training and periodic evaluations of the SOPs are recommended to improve the efficiency and accountability of the company’s cash management system.